Exploring Teacher’s Strategy in Teaching Listening through Songs at Eleventh Grade of SMA Walisongo Gempol - Vallyria Mamta Aulia; Fika Megawati (Applied Research on English Education (AREE), 2023)
English is one of the international languages that all people, especially students, must master. English is not only about reading but also speaking and listening. Therefore, listening material has been received up to the senior high school level since the junior high school level. In this listening lesson, a teacher must have the right and fun strategy in conveying material to students. In this study, researchers used interviews with teachers and made observations. The results of this study show that the two teachers have different strategies for conveying listening lessons. The first teacher used the 'Word Chain Song Game' strategy and the second teacher used the 'Guess the Meaning of Lyric' strategy. Each strategy is unique and has been adapted to class conditions and students' abilities. Listening comprehension is conveyed to students not only by listening to native speakers speaking but also by playing songs. Listening learning in this research, teachers use game-based learning strategies.  Keywords: Song, Listening, Teacher’s Strategy